Barriers and educational gaps in the provision of end-of-life care by emergency department nurses: A scoping review - Woods, Ashley; Santos Salas, Anna; Weisgerber, Lisa (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2026)
Background: The emergency department (ED) is regarded as unpredictable, chaotic, and unconducive to patient privacy. When patients present with end-of-life (EOL) care needs, nurses are not consistently educated or provided with the resources needed to give this type of care.Methods: One reviewer searched five databases. Titles, abstracts, and full texts were screened by one reviewer to yield 15 studies. Inclusion criteria based on emergency department nurses caring for adult patients within Canada, Australia, United Kingdom, and New Zealand, with no limit on publication date. Only literature written in English was included.Results: Emergency department nurses in Canada, Australia, United Kingdom, and New Zealand face similar challenges in the provision of EOL care. Research findings include the extensive environmental, educational, and communication barriers that work against the provision of EOL care by the ED nurse.Conclusion: With the most prevalent barriers being the ED environment, lack of education, and communication skills, nurses are not properly equipped through undergraduate or continuing education to provide good EOL care to patients and families. Education directed toward addressing barriers in communication, the environment and educational barriers will improve the experience of nurses providing care to patients at EOL in addition to their families. Research into the initiation of EOL education at the undergraduate nursing level may provide insight into institutional barriers and further inform the educational needs of current nurses.